Concentrações oscilantes de proteína bruta na dieta de ovinos - BARROS, Leonardo José Assis de (2021)
This study aimed to investigate feeding strategies aiming to increase nitrogen utilization efficiency through oscillating protein levels in the diet of sheep aiming to improve the dietary nitrogen utilization. The intake and digestibility of nutrients, feeding behavior, ruminal profile, nitrogen (N) balance, microbial protein synthesis (MPS), and the metabolic profile were measured in two experiments. Eight male cross-bred sheep were used in a 4x4 Latin square design. Four of them were castrated and canulated with average live weight of 58 kg ± 5.6 kg (mean ± SD) and four of them were not canulated and nor castrated with average live weight of 24.9 kg ± 1.3 kg. Treatments were composed of a control diet (CONTROL), with no dietary protein restriction over time; two levels of protein restriction over time: one with variation of 24 h and another of 48 h (T-24 and T-48, respectively); and a negative control (T-RESTRI) comprised of moderate protein restriction (20%) throughout the experiment. In both experiments, intake and apparent digestibility of dry matter, organic matter, total digestible nutrients, ether extract, neutral detergent fiber, and non-fiber carbohydrates did not differ (P > 0.05) across diets. The crude protein (CP) intake differed (P < 0.05) across diets, with T-RESTRI resulting in the lowest CP intake. In the second experiment, the CP digestibility (g/kg) was greater for T-48 than for CONTROL and T-RESTRI, while the T-24 diet resulted in CP digestibility intermediate between the CONTROL and T-48 diets. Ruminal ammonia nitrogen (N-NH3), pH, and volatile fatty acids (VFA) did not differ (P > 0.05) across treatments. The mean concentrations of VFA constituents resulted from the oscillating protein level diets (T-24 and T-48) had greater acetate and lower propionate when compared to the CONTROL and T-RESTRI diets. The nitrogen intake, urinary nitrogen, nitrogen balance, absorbed nitrogen, nitrogen efficiency utilization, ureic nitrogen, allantoin, xanthine + hypoxanthine, excreted purines, and MPS differed (P < 0.05) across treatments. The nitrogen intake, urinary nitrogen, nitrogen balance, absorbed nitrogen, nitrogen efficiency utilization, ureic nitrogen, allantoin, xanthine + hypoxanthine, excreted purines, and MPS differed (P < 0.05) across treatments. These variables were the lowest when animals were fed the TRESTRI diet. As for serum parameters, ureic nitrogen, aminotransferases, and proteins were not affected (P > 0.05) by diet. It is concluded that feeding oscillating protein in sheep diets did not result in modifications in the ruminal profile, except for the differences in the proportions of VFA components, primarily butyrate in the animals fed the oscillating protein diets, which indicates increased provision of endogenous nitrogen in the rumen. From the metabolic standpoint, the feeding strategy of oscillating protein levels did not imply positive benefits for the nitrogen balance in sheep fed those diets. Nonetheless, these strategies imply more labor and complexity to the daily feeding management of animals in the finishing phase. That suggests the need for more research in this area to confirm more precisely the effects of feeding oscillating nitrogen levels in the diet of sheep.